Sequential DNA methylation changes are associated with DNMT3B overexpression in colorectal neoplastic progression. Issue 4 (10th November 2010) - Ibrahim, Ashraf E K; Arends, Mark J; Silva, Ana-Luisa; Wyllie, Andrew H; Greger, Liliana; Ito, Yoko; Vowler, Sarah L; Huang, Tim H-M; Tavaré, Simon; Murrell, Adele; Brenton, James D
Abstract : Background and aims: Although aberrant methylation of key genes in the progression of colorectal neoplasia has been reported, no model-based analysis of the incremental changes through the intermediate adenoma stage has been described. In addition, the biological drivers for these methylation changes have yet to be defined. Linear mixed-effects modelling was used in this study to understand the onset and patterns of the methylation changes of SFRP2, IGF2 DMR0, H19, LINE-1 and a CpG island methylator phenotype (CIMP) marker panel, and they were correlated with DNA methyltransferase 3B (DNMT3B) levels of expression in a sample set representative of colorectal neoplastic progression. Methods: Methylation of the above CpG islands was measured using quantitative pyrosequencing assays in 261 tissue samples. This included a prospective collection of 44 colectomy specimens with concurrent normal mucosa, adenoma and invasive cancer tissues. Tissue microarrays from a subset of 64 cases were used for immunohistochemical analysis of DNMT3B expression. Results: It is shown that the onset and pattern of methylation changes during colorectal neoplastic progression are locus dependent. The CIMP marker RUNX3 was the earliest CpG island showing significant change, followed by the CIMP markers NEUROG1 and CACNA1G at the hyperplastic polyp stage. SFRP2 and IGF2 DMR0 showed significant methylation changes at the adenomatous polyp stage, followed by the CIMP markers CDKN2A and hMLH1 at the adenocarcinoma stage. DNMT3B levels of immunohistochemical expression increased significantly (p<0.001) from normal to hyperplastic and from adenomatous polyps to carcinoma samples. DNMT3B expression correlated positively with SFRP2 methylation (r=0.42, p<0.001, 95% CI 0.25 to 0.56), but correlated negatively with IGF2 DMR0 methylation (r=0.26, p=0.01, 95% CI −0.45 to −0.05). A subset of the CIMP panel ( NEUROG1, CACNA1G and CDKN2A ) positively correlated with DNMT3B levels of expression (p<0.05). Conclusion: Hierarchical epigenetic alterations occur at transition points during colorectal neoplastic progression. These cumulative changes are closely correlated with a gain of DNMT3B expression, suggesting a causal relationship.